Di-tert-Butyl 2,2′-[2,2′-methylenebis(naphthalene-2,1-diyldioxy)]diacetate - Qamar Ali; Itrat Anis; M. Raza Shah; Seik Weng Ng (Acta Crystallographica Section E, 2011)
In the title compound, C33H36O6, two naphthalene ring systems are connected through a methylene linkage [C—C—C = 114.9 (2)°]; the ring systems are aligned at an angle of 76.5 (1)°. Of the two –O–CH2–C(=O)–C(CH3)3 substituents, one adopts an extended conformation whereas the other is U-shaped. In the crystal, molecules are linked via weak C—H...O hydrogen bonding, forming supramolecular chains running along the c axis.